The role of culture-based learning on primary school students’ interest and understanding of Material Form concepts - Ali Topan, Rexsa; Kurnia Jayadinata, Asep; Ismail, Ali (Research in Physics Education, 2024)
This research was conducted to emphasize the significance of positive learning interest and deep understanding of concepts among students. Culture-based learning serves as an alternative pedagogical approach aimed at enhancing students’ interest and comprehension of concepts. Quantitative descriptive methodology was employed, utilizing a pre-experimental one-group pretest-posttest design. The research sample comprised fifth-grade students from a public elementary school in Indonesia. The research instruments included observation guidelines, questionnaires, and test questions. The findings revealed that the implementation of culture-based learning yielded an average score of 94%, indicating a very good outcome. Students’ interest in learning significantly improved following culture-based instruction, with an average score of 85.92%. Moreover, students’ understanding of concepts showed notable enhancement post-treatment, with average scores rising from 59% in the pretest to 81% in the posttest.